A bioinorganic investigation of some metal complexes of the Schiff base, N,N'-bis(3-methoxysalicylaldimine)propan-2-ol - Mopp, Estelle (Rhodes University, Faculty of Science, Department of Chemistry, 2010)
This thesis includes the synthesis, characterisation, antioxidant and antimicrobial activities of Cu(II)-, Co(II)- and Co(III) complexes with N,N'-bis(3- methoxysalicylaldimine)propan-2-ol, 2-OH-oVANPN. The Schiff base ligand, 2-OHoVANPN, is derived from o-vanillin and 1,3-diaminopropan-2-ol. The o-vanillin condensed with 1,3-diaminopropan-2-ol in a 2:1 molar ratio yields this potential tetraor pentadentate ligand. The complexes synthesized are tetra (or penta or hexa) coordinated. Formation of the complexes is symbolized as follows:- MXâ‚‚ + 2-OH-oVANPN (2:1) -> [M(2-OH-oVANPN)Xn] + HnX MXâ‚‚ + 2-OH-oVANPN (2:1) -> [Mn(2-OH-oVANPN)OH] + Hâ‚‚Xâ‚‚ MXâ‚‚ + (o-vanillin : diaminopropanol) (1:1) -> [M(1:1)Xâ‚‚] MXâ‚‚ + (o-vanillin : diaminopropanol) (1:1) -> [Mâ‚ƒ(1:1)Xâ‚„] M = Cu(II), Co(II) or Co(III); X = Cl; n = 1, 2. Their structural features have been deduced from their elemental analytical data, IR spectral data, and electronic spectral data. With the exception of {Cuâ‚ƒ(Câ‚ â‚ Hâ‚ â‚„Nâ‚‚Oâ‚ƒ)(Cl)â‚„(Hâ‚‚O)â‚†}(A4), the Cu(II) complexes were monomeric with 2-OH-oVANPN acting as a tetradentate ligand. A binuclear Co(II) complex, [Coâ‚‚(Câ‚ â‚‰Hâ‚ â‚‰Nâ‚‚Oâ‚…)(OH)] (B1), was synthesised and the rest of the Co(II) and Co(III) complexes were monomeric with chloride ions coordinating to the metal centre in some cases. Electronic data suggest that the cobalt(II) complexes have octahedral geometries and the copper(II) complexes have square planar structures "“ Co(III) is likely to be octahedral. Thermal analyses, which included the copper-block-method for determining sublimation temperatures, revealed that some copper(II) and cobalt(II) complexes are hygroscopic and sublime at 200 Â°C and below. DSC analyses of the Cu(II) complexes gave exotherms around 300 Â°C for complexes K[Cu(Câ‚ â‚‰Hâ‚‚â‚€Nâ‚‚Oâ‚…)(OH)]Â·2Hâ‚‚O (A1) and [Cu(Câ‚ â‚ H15Nâ‚‚Oâ‚ƒ)(Cl)â‚‚]Â·2Hâ‚‚O (A2) and above 400 Â°C for [Cu(Câ‚ â‚ Hâ‚ â‚†Nâ‚‚Oâ‚ƒ)(Cl)â‚‚] (A3) and {Cuâ‚ƒ(Câ‚ â‚ Hâ‚ â‚„Nâ‚‚Oâ‚ƒ)(Cl)â‚„(Hâ‚‚O)â‚†} (A4). Antioxidant studies were carried out against the 2,2-diphenyl-1-picrylhydrazyl radical (DPPHÂ·). The cobalt(II) complex, [Coâ‚‚(Câ‚ â‚‰Hâ‚ â‚‰Nâ‚‚Oâ‚…)(OH)] (B1), which was synthesized in the presence of KOH, had no antioxidant activity, whilst the other cobalt(II) complexes, [Co(Câ‚ â‚‡Hâ‚ â‚‡Nâ‚‚Oâ‚…(Cl))]Â·1Â½Hâ‚‚O (B2), [Co(Câ‚ â‚‰Hâ‚‚â‚‚Nâ‚‚Oâ‚…) (Cl)â‚‚]Â·5Â½Hâ‚‚O (B3) and [Co(Câ‚ â‚‰Hâ‚‚â‚‚Nâ‚‚Oâ‚…)(Cl)â‚‚]Â·5Â½Hâ‚‚O (B4), which were synthesised in the absence of KOH, demonstrated antioxidant activity. The latter complexes are candidates for cancer cell line testing, while [Cu(Câ‚ â‚ Hâ‚ â‚†Nâ‚‚Oâ‚ƒ)(Cl)â‚‚] (A3), {Cuâ‚ƒ(Câ‚ â‚ Hâ‚ â‚„Nâ‚‚Oâ‚ƒ)(Cl)â‚„(Hâ‚‚O)â‚†} (A4), [Co(Câ‚ â‚‰Hâ‚‚â‚ Nâ‚‚Oâ‚…)(Cl)â‚‚ ]Â·5Hâ‚‚O (C2) and [Co(Câ‚ â‚‰Hâ‚‚â‚€Nâ‚‚Oâ‚…)(Cl)]Â·3Hâ‚‚O (C3) may show anticancer activity through possible hydrolysis products. Most of the complexes synthesized displayed antimicrobial activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Aspergillus niger and Candida albicans. The results indicated that complexes [Cu(Câ‚ â‚ Hâ‚ â‚†Nâ‚‚Oâ‚ƒ)(Cl)â‚‚](A3), [Co(Câ‚ â‚‰Hâ‚‚â‚‚Nâ‚‚Oâ‚…)(Cl)â‚‚]Â·5Â½Hâ‚‚O (B3) and [Co(Câ‚ â‚‰Hâ‚‚â‚ Nâ‚‚Oâ‚…)(Cl)â‚‚ ]Â·5Hâ‚‚O (C2) are active against the Gram-negative Ps. aeruginosa and that the ligand, 2-OH-oVANPN, did not have any activity. The same trend was observed with 2-OH-oVANPN, {Cuâ‚ƒ(Câ‚ â‚ Hâ‚ â‚„Nâ‚‚Oâ‚ƒ)(Cl)4(Hâ‚‚O)â‚†} (A4) and [Co(Câ‚ â‚‰Hâ‚‚â‚€Nâ‚‚Oâ‚…)(Cl)]Â·3Hâ‚‚O (C3) against the Gram-positive S. aureus. As for activity against E. coli and C. albicans, some complexes showed more activity than the ligand. There is an observed trend here that the metal complexes are more active (toxic) than the corresponding ligand, which is in agreement with Tweedy's chelation theory.
Keywords: Schiff bases; Bioinorganic chemistry; Metal complexes; Transition metal complexes; Transition metals; Cancer -- Chemotherapy; Ligands -- Toxicity; Antineoplastic agents